Effects of olive leaf extract and nifedipine, alone and in combination, on blood pressure, neutrophil gelatinase-associated lipocalin, malondialdehyde, and creatinine levels in an Nω-nitro-L-arginine methyl ester-induced rat model of preeclampsia - Yetti Anggraini; Soetrisno Soetrisno; Brian Wasita; Risya Cilmiaty (Pensoft Publishers, 2024)
Preeclampsia (PE) is a significant health problem in pregnancy, affecting 6-7% of all gestations and leading to fetal growth retardation, infant morbidity and mortality, premature birth, and maternal death. Currently, effective treatment options for PE are limited. This study aimed to evaluate the therapeutic potential of olive leaf extract (OLE) and nifedipine, alone and in combination, in improving pregnancy outcomes in rats induced with Nω-nitro-L-arginine methyl ester hydrochloride (L-NAME). Rats were treated with single and combination treatments of nifedipine and OLE for four weeks, after being induced with L-NAME for six weeks. Following gestational day assessment and systolic blood pressure testing, the rats were sacrificed, and blood samples were collected for Neutrophil Gelatinase-Associated Lipocalin (NGAL), Malondialdehyde (MDA), proteinuria and Creatinine (SCr) Levels examinations. The results revealed the combination of nifedipine and OLE significantly improved the results of several biomarker analyses associated with PE, including increased NGAL levels, a significant decrease in MDA levels, decrease in proteinuria and elevated creatinine levels. The combination nifedipine and OLE treatment also exhibited a significant antihypertensive effect compared to either nifedipine or OLE monotherapy, as evidenced by the reduction in systolic and diastolic blood pressure levels. This study provides novel evidence for the potential of olive leaf extract as a nutraceutical adjunct for the prevention and treatment of PE. The significant improvements observed in several pathological features associated with PE, including antihypertensive effects, warrant further investigation. Future research should focus on elucidating the underlying mechanisms of action and exploring the clinical applicability of olive leaf extract in human populations with PE.